The orthodox Hegel development further developed - Theron, Stephen, 1939- (Cambridge Scholars Publishing, 2014)
This fifth book on Hegel assesses the consequences of Hegelian thought for spirituality. The fourth title in this series, Hegel's Philosophy of Universal Reconciliation (CSP 2013), recalled the more explicit phrase, ""to restore all things in Christ"", identifying the universal with the particular and, finally, the individual. This concreteness is the true universal. The ""double negation"", ""The Orthodox Hegel"", shows how the Christian movement, obliged by its own momentum to recognise its spiritual identity with the thought called, metonymously, ""Hegelian"", is Spirit itself impelling. As.